ANALISIS SISTEM PENCATATAN DAN PELAPORAN ONLINE TB/ HIV DI BBKPM SURAKARTA - Noor Alis Setiyadi; Jumadi -; Miftahul Arozaq; Fahmi Hakam; Bhisma Murti; Endang Sutisna Sulaeman (Universitas Muhammadiyah Semarang, 2015)
Introduction: Balai Besar Kesehatan Paru Masyarakat (BBKPM) Surakarta is a place providing health service including tuberculosis (TB) and human immunodeficiency virus (HIV). The application of recording and reporting running well will support providing, analysis and good of health service. Thus, the system analysis including input, process, and output are needed to provide it. Method: this study is descriptive with qualitative approach undertaken from Mei-July 2015 in BBKPM and distric health office, Sukoharjo. Data were obtained from in-depth interview and observation. The information were collected from 5 informans who choosed with purposive sampling technique. The validation of result was undertaken with triangulation method. Result and discussion: recording system of tuberculosis and human immunodeficiency virus in BBKPM had been using 3 kinds of software: SIM-RS, SITT and SIHA. In addition, the reporting data had been using the software from ministry of health, Indonesia. From them, there was no data spatial among BBKPM and distric health office in input and output. Disparity of software influence the work load, inefficiency in the data input and the redundancy occurs. Beside, the officers recorded manually to check the data input. Conclussion: there was no spatial data and work load in officer to record and report the data (input and process). In partiarcular of output, the officers were difficult to summary and present the data. The integration system in BBKPM and distric health office, Sukoharjo including spatial data were needed to support the surveillance process of TB/HIVKeyword : Tuberculosis, HIV, Recording, Reporting